O homem que calculava: uma abordagem recreativa para o ensino de matemática e suas dramatizações em sala de aula - Manzini, Tatiana Agenor (Universidade Federal de São Carlos, 2022)
The motivation and unfolding of this monograph is to address 4 problems from the book The Man Who Counted, analyzing and characterizing the conceptions that the author had in his time and that persist until today, for teaching in mathematics education. All this because the author, Malba Tahan, brings in his literature many explicit and implicit criticisms about the “traditional” approach to problem solving within the teaching of mathematics. And for that, we will deal with the absurdities and ironies that exist in this teaching-learning, in order to understand how to work this approach in an adequate way for reality, inside and outside the classroom. And as many problems in this book can be dramatized and problematized in different ways by students, the other motivation is to bring a collection of methodologies to approach this teaching, such as storytelling, classroom discussions or even group problem solving.
The man who counted: a recreational approach to mathematics teaching and its dramatizations in the classroom
Keywords: Malba Tahan; Álgebra; Homem que calculava; Ensino de matemática; Algebra; Man who counted; Mathematics teaching; CIENCIAS EXATAS E DA TERRA::MATEMATICA; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM::METODOS E TECNICAS DE ENSINO; CIENCIAS EXATAS E DA TERRA::MATEMATICA::MATEMATICA APLICADA::MATEMATICA DISCRETA E COMBINATORIA